The Effect of Laser Photodynamic Therapy on Treatment of Residual Cavities after Liver Echinococcectomy - Suvonkulovich, Toirov Abdukhamid; Zarifovich, Khamdamov Bakhtiyor (RA Journal of Applied Research, 2022)
Objective: To study the effectiveness of laser photodynamic therapy for the treatment of residual cavities after liver echinococcectomy. Materials and methods: An open prospective and retrospective study of clinical material was conducted using statistical and analytical methods of examination and treatment of 74 patients hospitalized in the Department of Surgery No. 1 of the Samarkand City Medical Association in the period from 2020 to 2021. Results: As a result, this method made it possible in our clinical studies to maximize the deposition of microorganisms, thereby preventing suppuration of the residual cavity and reducing the frequency of complications and relapses after liver echinococcectomy from 30 to 4.5%. Conclusions: Thus, the addition of laser photodynamic therapy in the treatment of liver echinococcosis is a highly effective combination of surgical and therapeutic methods of treatment, which provides a complete cure for patients and prevents the development of postoperative complications and relapses of the disease.